Os direitos sociais colocados em pauta na construção de metodologia para abrigo: a experiência da Fundação Criança de São Bernardo do Campo-SP - Gallo, Marcelo (2009)
This dissertação has as objective to analyze as a methodology of work in shelter was constructed that guideline in the guarantee of the rights in accordance with what this established in the Statute of the Child and the Adolescent. In this process we go to search to understand as that the city of Is Bernardo of the Field, that is reference in the social movements, the child remains per eight years executing works of attendance and to the adolescent, and only in 1998, it modifies the look for these boys and girls in the normative direction that compactua with the legal ones. The research has left of the participation of this researcher as subject of the research, of analyzes documentary, of individual interviews and the elaboration of focal group, that objectified to verify as we leave the irregular situation of children and adolescents and to the sprouting of citizens of rights. This analyzes makes possible to make the quarrel of the desconstrução of the model of irregular situation considered by the code of minors and the pressure of the social movements for efetivação of the integral politics for the right of the child and adolescent. Posterior to think as the city of They are Bernardo of the Field constructs politics you publish for infancy and youth, in the perspective of the guarantee of rights comes printing one practises politics. In this aiming I present of that it forms the city comes thinking and executed its action. The searched universe sample that from a new aiming politician actions consider who disassembles paradigms and places the right in the order of the day. For this we will go to dialogue with the professionals who had constructed these methodologies and to describe them, objectifying to contribute for the debate goes up the attendance the children and adolescents in abrigamento situation, mooring all quarrel who are made for the social movements in the construction of guarantee of rights